Localised intermittent upwelling intensity has increased along South Africa's south coast due to El Niño–Southern Oscillation phase state. Issue 3 (7th October 2019) - Duncan, MI; James, NC; Bates, AE; Goschen, WS; Potts, WM
Abstract : The El Niño –Southern Oscillation (ENSO) phase state is reported to drive interannual variability in sea temperatures along South Africa's south coast through its influence on wind-induced upwelling processes. Whether ENSO drives the intensity of localised, abrupt, intermittent upwelling is less well known. To explore this relationship, we used an index of localised, extreme (>2 °C anomaly), intermittent upwelling intensity, derived from in situ sea temperature data within the Tsitsikamma National Park Marine Protected Area, and quantified the relationship between annual cumulative upwelling intensities (1991–2013) with an annual ENSO index, namely the Southern Oscillation Index. We found that ENSO phase state modulates the cumulative intensity of extreme intermittent upwelling events during an annual period, with more and greater events during La Niña phases compared with El Niño phases. Furthermore, these extreme upwelling events have increased with time along South Africa's south coast as ENSO phase state becomes more intense and variable. Our findings support the emerging notion that the biological effects of climate change may be manifested through increased environmental variability rather than long-term mean environmental changes as ENSO is predicted to remain the dominant driver of local climate patterns in the future.